Demências: sob o domínio das lembranças - Zeppellini Junior, José Carlos (2013)
The present doctoral thesis is based on clinical experience and represents a deeper study of the research developed and presented in the master s dissertation Dementia: identities that sicken. Considerations about the psychopathologic aspects of the aging process defended in the Laboratory of Fundamental Psychopathology (Laboratório de Psicopatologia Fundamental), in the Program of Post-Graduation studies in Clinical Psychology at PUC-SP in 2008. The investigation of this work specifically focuses on the peculiarities of the psychic function that directly affects the mnemonic system of elder patients suffering from dementia processes. The point of view hereby defended is that the senile dementia processes are manifestations that are caused by the impossibility of forgetting, resulting in an imprisonment of the memory register. This perspective does not exclude the possibility that other dementia processes, classified as primary, have other forms of expressions and/or distinct genealogies. Nevertheless, it reveals that it is fundamentally important to consider the subjective aspects expressed by the dementia symptomatology. It points out the importance of taking these singularities into consideration in the treatments and demonstrates important aspects of the psychic apparatus concerning the mnemonic functions and the relation with pathos that becomes evident in the psychical working over related to aging (envelhescência). The distress, passion and excess inherent in the aging process send them to the conflicting encounter between the temporality of the body and non-temporality of the unconscious and also, of the ideal of the ego. This encounter may give stimulus to the formation of specific symptoms that will be activated in the senile dementia processes. They will be characterized by the refusal of the present time and the surrender of the ego to the magnificence of the memories from the past, recovered and strengthened by the increasing power of the superego